In-situ Primary Stress Detection Based on Seismic Tomography Measurements and Numerical Back-analysis for an Underground Radwaste Repository - Deák, Ferenc; Perras, Matthew A.; Bakai, János; Török, Ákos (Periodica Polytechnica Civil Engineering, 2023)
In order to understand how the in-situ primary stress state has evolved with subsidence and uplift in a granitic rock mass for anticipated of a radioactive waste repository in Hungary, the authors investigated the applicability of seismic tomography as an interpretive tool. Very high P wave velocity (Vp) values were obtained during the tomographic scanning of the study area of the repository, and these were compared with existing findings of in-situ and laboratory seismic measurements. Apart from seismic tomographic survey, dynamic FEM numerical modelling, empirical calculations of residual stresses, laboratory measurements of compression wave (ultrasonic) velocities on intact rock cores, in-situ primary stress measurements as well as site geological model were integrated to evaluate the use of seismic tomography for identifying possible in-situ stress increases around the excavation. A detailed calibration modelling was carried out based on the site seismic tomography measurements and during the large-scale modelling. It was observed that the increasing Vp is directly related to simulated increasing directional loadings on the rock mass. Using a measured wave raypath it was possible to check the different in-situ stress parametrizations which resulted in the best approximation to the measured Vp values. It was concluded that the rock mass under investigation to extend the repository must have higher in-situ stress values than the area of the constructed deposition chambers nearby. The results of this research indicated that seismic tomography is a useful tool for determining relative stress around and within the vicinity of underground excavation.